Dew observed on cars as a proxy for quantitative measurements. (December 2016) - Beysens, D.; Pruvost, V.; Pruvost, B.
Abstract: We describe a simple method to obtain absolute dew determination in any environment, based on observing dew formed at sunrise on cars. Cars are used as dew condensers where dew yield varies on three different parts that nearly all car exhibits: roof top, windshield and window side. The presence or absence of dew at the sunrise at these particular positions provides an observation scale index n with 4 levels, which is used to quantify dew yield. We show that the index n is proportional to the condensed dew volume h (mm) as measured on a standard planar condenser, inclined 30° from horizontal, following h = Kn . The validation of this scale and the determination of K (=0.067 mm within 20–30% uncertainty) is performed with long term experiments in different areas where dew is observed on several cars, either directly weighted on rooftops or calculated from meteo data. This method can thus be of great help to determine without sophisticated measurements or trained observers the dew potential in many places in the world, in particular in arid and semi-arid environment, where dew can help to answer water demand and means to evaluate the dew potential are often limited or lacking. Highlights: 4 levels quantitative dew measurements by simply observing car rooftop, windshield and side windows. Uncertainty is within 20–30%. The method can be used in nearly all parts of the world with few material needed and non-expert observers. The method can provide a valuable estimation of the dew potential of wide range of areas, even in remote areas. The plainness of the method is a powerful tool in all programs related to raising awareness concerning water issues.